2001
DOI: 10.1111/j.1745-9133.2001.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Firearms Violence Through Directed Police Patrol*

Abstract: Research Summary: This evaluation of a directed police patrol project utilizes a pre‐post quasi‐experimental design with a non‐equivalent control group as well as an interrupted time series analysis. The results suggest that directed patrol had an impact on firearms crime in one of the target areas but not the other. Policy Implications: The results suggest that a specific deterrence strategy whereby the police utilize directed patrol to focus on suspicious activities and locations reduced violent gun crime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 24 publications
4
125
1
Order By: Relevance
“…Therefore proactive strategies-confiscating illegally carried firearms by maximizing the number of police-citizen contacts, ensuing frisks, and/or ensuing searches of pedestrians or automobiles to increase detection of illegally carried firearms-seem like reasonable and effective police aims for preventing firearm violence (Kleck, 1991;Moore, 1980). Several published studies have found that enforcing laws forbidding carrying concealed weapons without a permit deters illegal firearm carrying and subsequent shootings (Cohen & Ludwig, 2003;McGarrell, Chermak, Weiss, & Wilson, 2001;Moore, 1980;Sherman & Rogan, 1995;Villaveces et al, 2000). Important questions about and limitations of this work, however, remain.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore proactive strategies-confiscating illegally carried firearms by maximizing the number of police-citizen contacts, ensuing frisks, and/or ensuing searches of pedestrians or automobiles to increase detection of illegally carried firearms-seem like reasonable and effective police aims for preventing firearm violence (Kleck, 1991;Moore, 1980). Several published studies have found that enforcing laws forbidding carrying concealed weapons without a permit deters illegal firearm carrying and subsequent shootings (Cohen & Ludwig, 2003;McGarrell, Chermak, Weiss, & Wilson, 2001;Moore, 1980;Sherman & Rogan, 1995;Villaveces et al, 2000). Important questions about and limitations of this work, however, remain.…”
Section: Introductionmentioning
confidence: 77%
“…Police claim that high levels of such police proactivity have crime-control benefits, and research tends to bear those claims out (Boydstun 1975; Sampson and Cohen 1988;Whitaker et al 1985; Wilson and Boland 1978; also see Cohen and Ludwig 2003;McGarrell et al 2001;Sherman and Rogan 1995;Rosenfeld et al 2014). But critics point to frequent violations of constitutional limits on police authority, and racially disparate impacts, as reasons to more closely regulate police-initiated contacts.…”
Section: Survey Methodologies the Police Services Surveymentioning
confidence: 99%
“…It is assumed that heightened surveillance and a greater police presence will lower violent crime (Marvell and Moody, 1996). Programs differ in specifics of operation, but a common strategy is to utilize patrol or traffic stops in order to search for illegal weapons and reduce firearms violence (Sherman and Rogan, 1995;McGarrell, Chermak, Weiss, and Wilson, 2001), or to monitor hot spots and decrease crime in general (Cordner, 1981;Sherman and Weisburd, 1995). Nightwatch can be considered a form of directed patrol, but the police work in concert with DJOs rather than alone.…”
Section: Chapter Two Program Descriptionmentioning
confidence: 99%